Disseminated and Congenital Toxoplasmosis in a Mother and Child With Activated PI3-Kinase δ Syndrome Type 2 (APDS2): Case Report and a Literature Review of Toxoplasma Infections in Primary Immunodeficiencies - Karanovic, Djuro; Michelow, Ian C.; Hayward, Anthony R.; DeRavin, Suk See; Delmonte, Ottavia M.; Grigg, Michael E.; Dobbs, Adam Kerry; Niemela, Julie E.; Stoddard, Jennifer; Alhinai, Zaid; Rybak, Natasha; Hernandez, Nancy; et al. (Frontiers in Immunology, 2019)
Phosphoinositide 3-kinase (PI3K) plays an integral role in lymphocyte function. Mutations in PIK3CD and PIK3R1, encoding the PI3K p110 and p85 subunits, respectively, cause increased PI3K activity and result in immunodeficiency with immune dysregulation. We describe here the first cases of disseminated and congenital toxoplasmosis in a mother and child who share a pathogenic mutation in PIK3R1 and review the mechanisms underlying susceptibility to severe T. gondii infection in activated PI3K syndrome (APDS) and in other forms of primary immunodeficiency.